2016
DOI: 10.1016/j.cpr.2016.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of online mindfulness-based interventions in improving mental health: A review and meta-analysis of randomised controlled trials

Abstract: Mindfulness-based interventions (MBIs) are increasingly being delivered through the Internet. Whereas numerous meta-analyses have investigated the effectiveness of face-to-face MBIs in the context of mental health and well-being, thus far a quantitative synthesis of the effectiveness of online MBIs is lacking. The aim of this meta-analysis was to estimate the overall effects of online MBIs on mental health. Fifteen randomised controlled trials were included in this study. A random effects model was used to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

58
685
10
24

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 821 publications
(777 citation statements)
references
References 73 publications
58
685
10
24
Order By: Relevance
“…In addition, odds ratio was computed to investigate the ratio of the odds of participant attrition in third-wave eHealth groups relative to comparator conditions. A power analysis revealed that a sample size of 146 participants is required to detect the difference in attrition rates suggested by the most relevant metaanalytic review that investigated participant dropout (16% vs. 37%; OR = 3.08; Spijkerman et al, 2016). In accordance, the current meta-analyses all had 100% power to detect this estimated ES at α = .05.…”
Section: Summary Measuressupporting
confidence: 51%
See 4 more Smart Citations
“…In addition, odds ratio was computed to investigate the ratio of the odds of participant attrition in third-wave eHealth groups relative to comparator conditions. A power analysis revealed that a sample size of 146 participants is required to detect the difference in attrition rates suggested by the most relevant metaanalytic review that investigated participant dropout (16% vs. 37%; OR = 3.08; Spijkerman et al, 2016). In accordance, the current meta-analyses all had 100% power to detect this estimated ES at α = .05.…”
Section: Summary Measuressupporting
confidence: 51%
“…In line with these findings, a recent meta-analytic review by Spijkerman et al (2016) found that online mindfulness-based interventions produced small to medium statistically significant benefits on depression, anxiety, and well-being outcomes at posttreatment relative to control conditions. In addition, this recent meta-analytic review also found that ESs did not significantly vary as a function of study population (i.e., nonclinical, somatic illnesses, or psychological illnesses).…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations